Treatment compliance of liver cirrhosis patients - Ye. R. Olevskaya; A. I. Dolgushina; A. N. Tarasov; D. S. Mikhaylova; A. R. Molchanova; A. S. Kuznetsova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To investigate treatment compliance of patients with the liver cirrhosis (LC). Material and methods. Overall 43 patients (17 men, 26 women) were enrolled to original study. Mean age of the patients was 47.1±11.9 years. Development of LC was the outcome of viral hepatitis, alcoholic liver disease and other diseases in 13, 14 and 16 patients respectively. Demographic features, disease duration, etiology, severity according to Child-Pugh score and «compliance level» questionnaire score were analyzed [Kadyrov R.V. et al., 2014]. Results. High level of dental compliance in LC patients was revealed (91.97±11.3), including emotional (32.52±4.4) and behavioral components (31.45±5.0). Social compliance level was estimated as average (28.00±3.6). No relation of treatment compliance to demographic features as well as to disease duration was found. The etiology of LC had no statistically significant impact on treatment compliance degree. Patients with LC of the Child-Pugh class B had highest compliance level (97.00±7.31), while those with Child-Pugh Class C - the lowest (80.89±11.73). Progression of encephalopathy exerts negative impact on treatment compliance. Emotional compliance of patients with the history of bleeding is significantly higher. Conclusions. Identification of factors that determine treatment compliance of LC patients is required for effective choice of treatment method and complication prophylaxis.